1976
DOI: 10.3758/bf03213188
|View full text |Cite
|
Sign up to set email alerts
|

Process training derived from a computer simulation theory

Abstract: Kotovskyand Simon (1973) identified four basic subprocesses in their computer simulation of adult and adolescent performance on Thurstone letter series completion problems. In Experiment I, children from Grades 1 to 6 were pretested on those problems, and then experimental subjects were trained on two of the four processes as an attempt to experimentally support a correspondence between the computer subroutines and human cognitive processes. A posttest administered in the experimental and control conditions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…It has been suggested that if the basic components of these required aptitudes can be identified and assessed, it may be possible to provide instruction that will remediate individual weaknesses. The effectiveness of such instruction in improving performance has been demonstrated in the case of analogy type test items (Sternberg & Ketron, 1982) and letter series completion items (Holzman, Glaser, & Pellegrino, 1976). There seems to be no evidence as yet, however, that this type of improvement in learning skills or aptitudes is generalized to new situations (Campione & Brown, 1978).…”
Section: Cognitive Processes Inmentioning
confidence: 95%
“…It has been suggested that if the basic components of these required aptitudes can be identified and assessed, it may be possible to provide instruction that will remediate individual weaknesses. The effectiveness of such instruction in improving performance has been demonstrated in the case of analogy type test items (Sternberg & Ketron, 1982) and letter series completion items (Holzman, Glaser, & Pellegrino, 1976). There seems to be no evidence as yet, however, that this type of improvement in learning skills or aptitudes is generalized to new situations (Campione & Brown, 1978).…”
Section: Cognitive Processes Inmentioning
confidence: 95%
“…Several computer programs, for example, have been devoted exclusively to the solution of analogies (Evans, 1968;Reitman , 1965) o~ series completions (Simon ~ Kotovsky, 1963), and other computer problems have dealt with analogies or series completions, among other kinds of problems ( Williams , 1972;Winston , 1974). Analogy problems have been studied experimentally in a number of investigations with human subjects (e .g., Moiholland , Pellegrino , $ Chaser , in press; Sternberg, a, 1977bWhitely ~ Barnes, 1979), as have series completions (e.g., Holzman, Chaser, ~ Pellegrino, 1976;Kotovsky ~ Simon, 1973). We are unaware of any previously published information-processing analyses of the classification task, although Pellegrino and his colleagues are currently studying this task (Pe hlegrino , Note 1), and the literature on concepts and thel attainment can be viewed as indirectly studying this sort of task (e.g.…”
Section: Unities In Inductive Reasoningmentioning
confidence: 99%
“…There can be little doubt that some training of cognitive processes is both possible and feasible (see, e.g., Borkowski & Cavanaugh, 1979;Feuerstein, 1979;Holzman, Glaser, & Pellegrino, 1976). Although evidence supporting the durability and generalizability of such training is still i;eager, we have cause to be at least modestly optimistic regarding the feasibility of training some cognitive skills (Bro-,.…”
mentioning
confidence: 99%